Contingent Reward Transactional Leaders as “Good Parents”: Examining the Mediation Role of Attachment Insecurity and the Moderation Role of Meaningful Work - Lopez-Bohle, S (Springer New York LLC, 2019)
Deriving from the analogy between contingent reward transactional leaders (featured by clarity, consistency, consideration, and consequences) and “good parents,” we develop a moderated mediation model where attachment insecurity (avoidance and anxiety attachment) mediates the relationship of contingent reward transactional leadership with follower job insecurity, burnout, job performance, and organizational citizenship behaviors, and meaningful work moderates the relationship between contingent reward transactional leadership and attachment insecurity. Results based on two-wave data from two independent samples largely support our hypotheses. Specifically, supporting attachment theory, the relationship of contingent reward transactional leadership and follower outcomes (i.e., job insecurity, burnout, and job performance) is mediated by both avoidance attachment and anxiety attachment. Supporting the contingency theory of leadership, meaningful work strengthens the relationship between contingent reward transactional leadership and avoidance and anxiety attachment. Additionally, the indirect effect of contingent reward transactional leadership and follower outcomes via avoidance and anxiety attachment is contingent upon meaningful work. © 2018, Springer Science+Business Media, LLC, part of Springer Nature.